Digital and media literacy competences: A study with basic education students - Matos, A.P.M.; Seixas, A.; Festas, I.; Bobrowicz-Campos, E.; Tomé, V. (https://ecrea.eu/news/10283103, 2021)
The pace of digital technologies evolution and the widespread and inevitability of its use by citizens in the most diverse spheres of life, in a society whose dynamics are themselves highly mediatized, and often created and recreated on and for screens, have made media literacy a privileged subject for discussion and reflection and an object of various initiatives in terms of national and international educational policies. At an international level, the recommendations and directives produced in recent decades by different entities (e.g., UNESCO, European Commission, United Nations) highlight the need and relevance of promoting the digital and media literacy competences of citizens of all ages and encourage countries to invest in empowering them through media education, as well as to develop empirical research to assess their digital and media literacy competences, and thus to contribute to more informed action based on their real needs. This study was conducted in the frame of the COMEDIG project (PTDC/CED-EDG/32560/2017), which was designed to assess digital and media literacy competences in the Portuguese school community and, based on the assessment results, to elaborate recommendations for future comprehensive intervention, as well as digital educational resources. Given the wide range of project objectives, this paper will focus on presenting and discussing some of the results of the cross-sectional study carried on to characterize digital and media literacy competences of students from basic education and identify their needs for further training. For this purpose, a national stratified sample of approximately 3000 students from the 1st, 2nd and 3rd cycles of basic education was selected. The participants fulfilled online questionnaires examining their competences in media uses, critical reading (associated with comprehension and evaluation of media products) and expression (involving communication, participation, and creation of media contents), elaborated by the research team. The assessment questions were prepared based on literature review, and on the results of mapping media education contents present (i) in the core curriculum of Portuguese basic education, homologated in 2018, and (ii) in the educational projects developed by schools that in the academic year 2017/2018 integrated the Autonomy and Curriculum Flexibility Project. These questions also considered the social meanings, perceptions, attitudes, and opinions of students and teachers with regard to media, collected through focus group interviews, in the context of an exploratory study conducted in the first phase of the COMEDIG project. In this presentation, the study authors will present some of the findings that emerged from the study, adopting a comparative perspective of the different cycles of basic education. The results will be discussed taking into account the previous research on this subject, giving particular emphasis to their practical implications for educational policies and practices.